Learning curve for gastric cancer patients with laparoscopy-assisted distal gastrectomy: 6-year experience from a single institution in western China. Issue 37 (September 2016) - Zhao, Lin-Yong; Zhang, Wei-Han; Sun, Yan; Chen, Xin-Zu; Yang, Kun; Liu, Kai; Chen, Xiao-Long; Wang, Yi-Gao; Song, Xiao-Hai; Xue, Lian; Zhou, Zong-Guang; Hu, Jian-Kun
Abstract : Abstract: Laparoscopy-assisted distal gastrectomy (LADG) is widely used for gastric cancer (GC) patients nowadays. This study aimed to investigate the time trend of outcomes so as to describe the learning curve for GC patients with LADG at a single medical institution in western China over a 6-year period. A total of 246 consecutive GC patients with LADG were divided into 5 groups (group A: 46 patients from 2006 to 2007; group B: 47 patients in 2008; group C: 49 patients in 2009; group D: 73 patients in 2010; and group E: 31 patients in 2011). All surgeries were conducted by the same surgeon. Comparative analyses were successively performed by Mann–Whitney U test or Student t test among the 5 different groups for the clinical data, including clinicopathologic characteristics, surgical parameters, postoperative course, and survival outcomes, through which the learning curve was described. There were no differences in the baseline information among the 5 groups ( P > 0.05), and the proportion of advanced GC patients with LADG slightly increased from 58.7% to 77.4% during the 6 years. Besides, the proportion of D2/D2+ lymphadenectomy and the number of retrieved lymph nodes gradually grew from 60.9% to 80.6% and from 20.0 to 28.8, respectively. In addition, the operation time decreased from 299.2 to 267.8 minutes, while the estimated blood loss dropped from 175.2 to 146.8 mL. Furthermore, some surgical parameters (surgical duration and blood loss) and postoperative course (such as postoperative complications, the time to ambulation, to first flatus, and to first liquid intake as well as the length of hospital stay) were all observed to be significantly different between group A and other groups ( P < 0.05), illustrating a similar downward trend and remaining stable to form a plateau after 46 cases in group A. However, no difference on overall survival was found among these 5 groups, and multivariate analysis indicated that factors, such as age, tumor differentiation, tumor size, and T stage as well as N stage, were independent prognostic factors for patients with LADG. Improvement on surgical parameters and postoperative course can be seen over the past years, and the cutoff value of the learning curve of LADG for surgeons with rich experience in open operation might be 46 cases. Abstract : Supplemental Digital Content is available in the text